2013
DOI: 10.1016/j.febslet.2013.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Fast prediction of deleterious angiogenin mutations causing amyotrophic lateral sclerosis

Abstract: a b s t r a c tCertain single nucleotide polymorphisms causing missense mutations in angiogenin result in its loss-of-function and onset of amyotrophic lateral sclerosis (ALS). Although several such associations are reported across diverse ethnic groups, no method is available for predicting if a new mutation is deleterious. We present here a fast molecular dynamics based method for determining the mechanisms of functional loss caused by mutations, and attributes to ascertain whether a mutation causes ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
(112 reference statements)
2
17
0
Order By: Relevance
“…Since its first discovery by Greenway et al 5 , the ANG gene has emerged as one of the most frequently mutated genes found in ALS patients of diverse ethnic groups. A total of 19 missense mutations in ANG have been associated with ALS 6, 7 . In addition, several rare mutations have also been discovered in the ANG gene; however, it is not yet known whether these are instrumental in causing ALS 7 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since its first discovery by Greenway et al 5 , the ANG gene has emerged as one of the most frequently mutated genes found in ALS patients of diverse ethnic groups. A total of 19 missense mutations in ANG have been associated with ALS 6, 7 . In addition, several rare mutations have also been discovered in the ANG gene; however, it is not yet known whether these are instrumental in causing ALS 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 19 missense mutations in ANG have been associated with ALS 6, 7 . In addition, several rare mutations have also been discovered in the ANG gene; however, it is not yet known whether these are instrumental in causing ALS 7 . The human ANG gene encodes a 14.1 kDa long monomeric ANG protein that induces neovascularization, maintains the physiology and health of motor neurons by inducing angiogenesis, stimulates neurite outgrowth and path-finding and protects motor neurons from hypoxia-induced death and hence acts as a neuroprotective factor 812 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations